Contractors' Perspective on the Benefits of Implementing Industrialized Building System (IBS) - Hanafi, Mohd Hanizun; Abdullah, Shardy; Abdul Razak, Arman (International Journal of Sustainable Construction Engineering and Technology, 2015)
Construction industry is considered among the most crucial sectors in developing countries where it is capable to drive a nation towards progressive development as it provides a positive platform to other industries. Implementation of Industrialized Building System (IBS) has been acknowledged as an effective measure to increase capability within the industry as compared to the conventional methods. The purpose of this study is to present the benefits of implementing IBS from contractors’ viewpoint. Questionnaire forms were distributed to 683 construction firms registered under the Construction Industry Development Board of Malaysia operating in the states of Penang, Selangor, Kuala Lumpur and Johor. A total of 254 questionnaire forms were returned duly completed. The collected data was analysed using the Conformity Index. Three main benefits gained by implementing IBS from the contractors’ perspective are (1) IBS increases the productivity of construction works, (2) IBS reduces concrete mixing activities at construction sites and (3) IBS reduces the overall duration of construction work. These results indicate that the contractors are focusing more on completing construction works with the help of IBS implementation at construction sites. Also with IBS, it is able to minimize the problem of site mismanagement/disorganization through a significant reduction of in-situ wet concrete works.